Hospitalized fracture rates amongst patients with chronic kidney disease in Australia using data linkage. Issue 6 (1st December 2019) - Lin, Raymond; Toussaint, Nigel D.; Gallagher, Martin; Cass, Alan; Kotwal, Sradha
ABSTRACT: Background: Renal osteodystrophy leading to fractures in chronic kidney disease (CKD) is associated with significant hospitalization, morbidity, mortality and health care costs. There is a paucity of data on fractures in the CKD population in Australia. Aim: To describe the trends and impact of hospitalized fractures in an Australian population of non‐dialysis CKD patients. Methods: Retrospective observational data derived using data linkage. Fracture rates, trends in hospital admissions, comorbidity burden and mortality were analysed in a non‐dialysis CKD population between 2000 and 2010 in the Australian state of New South Wales. Hospitalized patients with CKD and fractures were compared with CKD patients without fracture. Results: A total of 149 839 hospitalized patients with CKD were included, of whom 9898 (6.6%) experienced one or more fractures. Patients with fracture were older, more likely to be female with a higher comorbidity burden than those without. Hospital admissions involving fracture were longer than non‐fracture admissions (14.3 vs 5.9 days, P  < .0001) and patients were less likely to be discharged home (28.3% vs 80.9%, P  < .0001). The 12‐month mortality rate was high at 41%. Conclusion: Australian non‐dialysis CKD patients with hospitalized fractures were older, had a greater burden of disease, and have similar rates of fracture and associated mortality compared to international CKD cohorts. Implications of fracture requiring hospitalization are considerable, with longer admissions, greater healthcare costs, lower likelihood of discharge home and significant mortality. As fracture prevention in the CKD population evolves, treatment algorithms should account for those at greatest risk. SUMMARY AT A GLANCE: Among 6.6% of 149 839 hospitalized patients with non‐dialysis chronic kidney disease (CKD), fracture risks expectedly included old age, female gender and a higher comorbidity burden. They have similar rates of fracture and associated mortality compared to international CKD cohorts.